Validation and reliability of the 12-item Zarit burden interview among informal caregivers of elderly persons in Nigeria (2018)
Research on ageing in Nigeria has shown that informal care places economic and psychological strain on the caregivers of the elderly persons. However, objective method of assessment of the burden of care for the elderly among caregivers is lacking. This study was aimed at validating the 12-item Zarit Burden Interview (ZBI) among caregivers of elderly persons in Nigeria in correlation with the Katz Index of Independence in Activities of Daily Living (Katz-ADL), the General Health Questionnaire (GHQ-12) and the Modified Conflicts Tactics Scale for Elder Abuse (MCTS). Eighty primary caregivers of community-dwelling elders were selected using a two-stage cluster sampling from two communities. Principal component analysis with varimax rotation was used to determine the factor structure of the ZBI. Construct validity was assessed using Spearman’s correlations between the ZBI, the GHQ-12, Katz ADL and MCTS. Internal consistency and instrument reliability were examined with the Cronbach’s alpha split-half correlation. Three factors with eigenvalues greater than 1.0 were extracted on the exploratory factor analysis comprising all 12 items accounting for 68.0% of the total item variance. The reliability analysis gave a Cronbach’s α of 0.90 and a split-half correlation coefficient of 0.84. Spearman’s correlation (rs) showed good correlation between the ZBI scores and GHQ-12 (rs=0.44, p<0.001), MCTS (rs=0.43, p<0.001) and Katz ADL (rs= -0.50, p <0.001). The 12-item ZBI is a valid and reliable tool for assessing burden in informal settings among caregivers of elderly persons. The tool can be used to assess burden of care among caregivers of elderly persons in community settings.